Blue cooperative upconversion and white light emission from Y2Si2O7:Yb3+ nanopowders due to 975-nm infrared excitation - (:unkn) unknown (SPIE-SOC PHOTO-OPTICAL INSTRUMENTATION ENGINEERS, 2016)
We report the luminescence properties of undoped and 10% Yb3+-doped Y2Si2O7 nanopowders under the infrared excitation of 975-nm laser diode. A broadband white light (WL) emission is observed in the undoped powder, and its intensity becomes stronger with increasing excitation power. A blue emission centered at similar to 475 nm is observed below the excitation power of similar to 2 W in the Yb3+-doped sample. The blue emission intensity dependence on the excitation power suggests that this emission is a two-photon absorption process known as the cooperative luminescence of Yb3+ ions. When the excitation power is increased above 2 W, a broadband white emission extending from blue into the near infrared appears while the blue cooperative emission band of Yb3+ ions disappears. The excitation power dependence of the WL intensity at 758 nm is due to a multiphoton process that may be attributed to the thermal radiation mechanism. The International Commission on Illumination coordinates (x,y) for the WL emission in the Yb3+-doped Y2Si2O7 nanocrystalline sample is found to be (0.4503, 0.3999) and (0.5035, 0.4096) for 2.005- and 3.68-W excitation powers, respectively. These values lie in the yellowish region and correspond to the color temperature value of 5030 K, with a color rendering index of 85. (C) 2016 Society of Photo-Optical Instrumentation Engineers (SPIE)
Keywords: Y2Si2O7;Yb3+; laser spectroscopy; white light emission; LUMINESCENCE; POWDERS; BRIGHT; ER3+; YB3+